Socio-economic conditions and LGU responses to urbanization of the Municipalities of Leganes, Oton, Pavia, and San Miguel before and after the formation of Metro Iloilo-Guimaras Economic Development Council (MIGEDC) - Acosta, Mabelle Esconde
Urbanization is a process which promotes economic growth and development. On the other hand, it has its corresponding externalities spilled over from the urban areas to the adjacent locales. One of the management strategies used by the local government units (LGUs) in order to address the overwhelming consequences of urbanization is alliance formation. Limited studies were conducted to establish socio-economic contributions of urbanization to the suburban areas. This study aims to describe and compare the socio-economic condition and LGU responses to urbanization of the municipalities of Oton, Leganes, Pavia, and San Miguel before and after formation of Metro Iloilo-Guimaras Economic Development Council (MIGEDC). The result of the study showed that there is a need for greater collaboration in various areas such as: land use management in accordance to each municipality's special functional role; water and energy management to foster economies of scale; health services since rthe pressing problem of air pollution excludes no one; public safety services to establish a functional disaster and crime prevention system; environmental management for sustainable development; infrastructure services for complementary plans and projects; and investment opportunity promotions. Communication and education services need not be further integrated when it comes to managing the externalities of urbanization in Iloilo City.